Participation of Special Needs Communities in the 2019 Legislative Elections in Medan City - Ishaq Abrar Mustafa Tarigan; M. Arif Nasution; Heri Kusmanto (PERSPEKTIF, 2023)
This article explores the participation of individuals with special needs/disabilities in the 2019 legislative elections in Medan City. Despite numerous regulations governing the rights and participation of disabled voters in elections, their political rights, particularly the right to vote, are often overlooked in practice. This is evident in their low participation rates in elections, especially in Medan City. The research aims to assess the level of participation and political behavior of disabled individuals in elections and evaluate the efforts of the Medan City Election Commission (KPU) in enhancing their participation. The research method employed is qualitative descriptive, using interviews and in-depth analysis as data collection techniques. The findings indicate inaccurate data regarding disabled individuals in Medan City and low participation rates due to the lack of professionalism among polling station officers in data collection and services. This study recommends recruiting polling station officers based on qualifications and relevant experience to provide maximum and professional services in their duties. The data updating process should also be improved through collaboration between election organizers, the Department of Social Affairs, and the Department of Population and Civil Registration to collect data on disabled individuals in Medan City more effectively. Furthermore, election organizers should engage in outreach efforts,